2018
DOI: 10.1016/j.cels.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phase Separation Provides Long-Term Memory of Transient Spatial Stimuli

Abstract: Protein/RNA clusters arise frequently in spatially regulated biological processes, from the asymmetric distribution of P granules and PAR proteins in developing embryos to localized receptor oligomers in migratory cells. This co-occurrence suggests that protein clusters might possess intrinsic properties that make them a useful substrate for spatial regulation. Here, we demonstrate that protein droplets show a robust form of spatial memory, maintaining the spatial pattern of an inhibitor of droplet formation l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 36 publications
5
104
0
Order By: Relevance
“…Recently, it was demonstrated that colloidal protein behavior has an essential role in self-assembly processes, as occurs in condensation and Ostwald ripening [ 33 , 34 ]. Ostwald ripening explains the formation of protein droplets in a liquid system, such as the nucleolus or the cytoplasm, and is of great importance in cellular physiology and stress response [ 35 ].…”
Section: Setting the Frame And Initial Considerationsmentioning
confidence: 99%
“…Recently, it was demonstrated that colloidal protein behavior has an essential role in self-assembly processes, as occurs in condensation and Ostwald ripening [ 33 , 34 ]. Ostwald ripening explains the formation of protein droplets in a liquid system, such as the nucleolus or the cytoplasm, and is of great importance in cellular physiology and stress response [ 35 ].…”
Section: Setting the Frame And Initial Considerationsmentioning
confidence: 99%
“…These MLO condensates are structurally stable but their protein and RNA constituents exchange dynamically with the surrounding nucleoplasm. Their formation can be highly cooperative in response to small changes, a feature frequently observed during transitions in biological systems, and used by cells to amplify or extend transient signals (Dine, Gil, Uribe, Brangwynne, & Toettcher, ). It seems possible that the underlying molecular recognition mechanism might be sequence‐dependent (Fei et al, ; Wang et al, ) but this is challenged by mutagenesis experiments that compromise amino acid sequence and overall composition (Pak et al, ).…”
Section: Cellular Spatial Organization Depends On Biological Self‐orgmentioning
confidence: 99%
“…They also reveal two distinct classes of optoNBs, those for which binding occurs in the light and others for which it occurs in the dark. The ability to induce binding by switching to dark conditions is rare, as most previously-developed optogenetic tools exhibit light-induced binding; yet the few existing light-suppressible optogenetic tools available 23,24 have already proven useful for probing T cell signaling 25 , controlling metabolic flux 26,27 , and studying the consequences of protein phase separation 15 . Photoswitchable domain insertion thus holds promise for engineering light-based control of protein-protein interactions.…”
Section: Initial Optonbs Exhibit Weak Light-switchable Binding As Welmentioning
confidence: 99%
“…Nearly 20 years after the initial development of light-regulated transcription in yeast 1 and light-gated ion channels in neuroscience 2 , optogenetics has been extended to almost every corner of cell biology. Optogenetic proteins are now available to control the fundamental currencies of protein heterodimerization [3][4][5] , homo-dimerization 6,7 , gene expression 1,8,9 , degradation 10 , nuclearcytosolic translocation [11][12][13][14] , and even liquid-liquid protein phase separation 15,16 . These techniques have enabled a new generation of precise perturbation studies to interrogate how the timing, spatial location, and identity of active proteins alter cellular and developmental processes.…”
Section: Introductionmentioning
confidence: 99%